2015
DOI: 10.1037/a0039432
|View full text |Cite
|
Sign up to set email alerts
|

The way films feel: Aesthetic features and mood in film.

Abstract: Audiences often speak of the "atmosphere," "tone," or "mood" of films, and scholars have suggested that a film's mood is related to its aesthetic presentation. In this exploratory study, we investigated how aesthetic features of film relate to one another and contribute to film mood. Participants assessed 14 film clips according to their perceived mood as well as 27 aesthetic features: 13 so-called low-level features related to specific stylistic devices of film and 14 high-level abstract features general to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
(99 reference statements)
3
15
0
1
Order By: Relevance
“…Many other laboratory studies have shown that motion also captures attention (see, for example, Franconeri & Simons, 2003), which has also been shown for people watching sections of movies (Mital, Smith, Hill, & Henderson, 2011). Still other controlled studies have shown that we have positive associations to brightness and negative associations to darkness (Valdez & Mehrabian, 1994), a finding also found for people watching short movies (Tarvainen, Westman, & Oittinen, 2015). Rapid transients (cuts), motion changes, and luminance changes have been endemic to movies for a century, and they are components of what film editors call pace .…”
Section: Significancesupporting
confidence: 71%
See 1 more Smart Citation
“…Many other laboratory studies have shown that motion also captures attention (see, for example, Franconeri & Simons, 2003), which has also been shown for people watching sections of movies (Mital, Smith, Hill, & Henderson, 2011). Still other controlled studies have shown that we have positive associations to brightness and negative associations to darkness (Valdez & Mehrabian, 1994), a finding also found for people watching short movies (Tarvainen, Westman, & Oittinen, 2015). Rapid transients (cuts), motion changes, and luminance changes have been endemic to movies for a century, and they are components of what film editors call pace .…”
Section: Significancesupporting
confidence: 71%
“…It has been shown that people have positive associations to brightness and negative associations to darkness (Valdez & Mehrabian, 1994). More importantly, this has also been found for people watching short movies (Tarvainen et al, 2015). Thus, the empirical foci of this paper are those correlated with filmmakers’ notions of pace: shot duration, motion, and luminance.…”
Section: Movies Psychology and Pacesupporting
confidence: 54%
“…Also, valence, energetic arousal, and tense arousal ratings of music and speech have been found to be greater in the case of loud samples than quiet ones [21]. The results of our earlier preliminary study on the determinants of film mood echo these findings by indicating that stylistic attributes in particular are related to film mood [22].…”
Section: Relation To Film Moodsupporting
confidence: 58%
“…However, since this concept of an "art mood" has only recently gained popularity in film studies [10], [11], there is not much precedent in the use of dimensional affect models in the assessment of film mood. One exception is our earlier study [22], which used the UWIST Mood Adjective Checklist [26]. In this method, mood is assessed indirectly by way of 24 descriptive terms such as "happy" and "depressed", and the item ratings can then be transformed to mood ratings in the HT, EA, and TA dimensions.…”
Section: Assessment Of Film Moodmentioning
confidence: 99%
See 1 more Smart Citation